Thermal Oxidation Curing of Polycarbosilane for SiOC Fiber Process - Shin, Dong-Geun (Asian Journal of Chemistry, 2014)
Two types of polycarbosilane having a different molecular weight were prepared from polydimethylsilane in the presence of zeolite as a catalyst and additional heating at 400 ºC for 5-15 h. They were compared the thermal oxidation behaviour to optimize the curing condition for SiC fiber fabrication process. From the thermogravimetry analysis, the weight of low Mw polycarbosilane (PCS_1) was rapidly increased and decreased than that of high Mw polycarbosilane (PCS_2) which represents that oxygen act as a cross-linking among react with methyl in the polycarbosilane molecule caused to rapid increase whereas they are also decomposed in the form of alkane (C2H6) or methane (CH4) at the temperature up to 350 ºC, which leads the total weight decrease in PCS_1. For the isothermal oxidation of PCS_1, weight gain at 200 ºC was consistently increased with isothermal time and reached to 13 wt % after 5 h. From SEM and XRD results, SiOC fibers obtained by pyrolysis at 1200 ºC in Ar showed clean surface and a typical fracture behaviour of glassy phase which represent an excellent mechanical strength.